Influence of public infrastructure, education and health on poverty in Central Maluku district - Sangadji, Maryam; Nikijuluw, Jeanee Belthia; Ramly, Fahrudin; Yurinawati, Dwi Evita (Central Research Institute for Agriculture (CeRIA), 2024)
Poverty is a very complex problem, which is not only caused by a lack of income and assets, but also due to non-income factors, one of which is a lack of access to public services and welfare facilities. This research aims to determine the influence of public infrastructure, education and health on poverty in Central Maluku Regency. The data analysis method uses secondary data, time series which is quantitative data with a Multiple Linear Regression analysis model. The results of this research show that partially the Realization of Capital Expenditures as a variable measure of public infrastructure has a positive and significant effect on poverty, apart from that the Average Years of Schooling as a measure of the Education variable also shows a positive but not significant effect, while the Life Expectancy Rate as a Measure of the Health Variable shows the results of a negative and significant influence on poverty in Central Maluku Regency 2013-2022.